การจัดพิธีสรงกู่โดยชุมชน ชุมชนกู่กาสิงห์ ตำบลกู่กาสิงห์ อำเภอเกษตรวิสัย จังหวัดร้อยเอ็ด - วรรณโชติ วชิราภรณ์; รัตนสุธีระกุล กนกพร; ไชยศิรินทร์ สายไหม; ชีวาพัฒนานุวงศ์ พรศิริ (Area Based Development Research Journal, 2016)
บทคัดย่อไม่สมบูรณ์ The Songku Ceremony by Kukasing Community, kukasing Sub-district, Kasetwisai District, Roi Et Province The Songku ceremony must start with creating understanding among community members on the importance of the ceremony which is different from the Songkran festival. The Songku ceremony must follow traditional practice and has to organize by people in Kukasing community. The process of ceremony must follow a correct and clear pattern, which will be used for organizing the ceremony in the next year. In order to persuade local people to join the ceremony, before a ceremony day there must have a meeting of the committee, who are natives of Kukasing, to prepare public relations work. In the morning of the ceremony day there will have a spirit worship to show respect to the holy object of ancient remains. The event will follow by the Songku ceremony, which will begin with religious ceremony such as the monks pray for holy thing. A leader of the ceremony will lead participants to worship and ask for forgiveness to ancient remains. After that villagers will pour scented water onto the monks’ hands and then monks will take villagers to watering various parts of ancient remains. During the ceremony, there will be no garbage dispose around ancient remains, the expression of disrespect to the place. Traditional conservation should aim at building understanding among kids and youths in the Kukasing community via educational activities on local tradition, encourage kids and youths to participate the ceremony via activities that they are interested in such as competition related to the Songku ceremony.